PENERAPAN TEORI KEPUTUSAN DALAM MODEL PENGAMBILAN KEPUTUSAN TERKAIT MASALAH EKONOMI PERTAHANAN: Konsep Pohon Keputusan - Susdarwono, Endro Tri; Setiawan, Ananda (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
The shift in global paradigm and threat perspective has led to a wide variety of possible risks and uncertainties. This situation also occurs in the defense economy, so understanding the basic principles of risk and uncertainty is important, especially in a decision-making process. There are several elements and concepts that are usually used in all decision models. Almost all models, whether complex or simple, can be formulated using a standard structure and solved by using general evaluation procedures. For decisions involving a series of decisions and relating to various basic sequential conditions, the decision tree is an appropriate conceptual and schematic modeling tool. A decision tree is a schematic representation of a decision problem. A decision tree is a diagram made like a tree with branches and branches in a chronological order of events, with each having a choice and possibility of occurrence, as well as the results of each choice. The term decision tree is taken from the form of diagrams that have branches and twigs, just like a tree.